The expression of a mountain cedar allergen comparing plant-viral apoplastic and yeast expression systems - Moehnke, Marcie H. (2008)
Jun a 3, a major allergenic protein in mountain cedar pollen, causes seasonal allergic rhinitis in hypersensitive individuals. Recombinant Jun a 3 was expressed in Nicotiana benthamiana interstitial fluid (300 μg/g leaf material) and Pichia pastoris (100 μg/ml media). Polyclonal anti-Jun a 3 and IgE antibodies from the sera of allergic patients both reacted with the recombinant protein. Of the two systems, recombinant protein from the plant apoplast contained fewer contaminating proteins. This method allows for a more convenient and inexpensive expression of the recombinant allergen, which will allow for further structural studies and may prove useful in diagnostic and/or immunotherapeutic strategies for cedar allergy.